SISTEM INFORMASI PENGOLAHAN DATA KULIAH KERJA MAHASISWA DI LP3M UNIVERSITAS BANTEN JAYA BERBASIS WEB - Sutanto Sutanto; Yul Hendra; Miftahul Jannah (LPPM Unbaja, 2021)
Student Work Lecture (KKM) is one of the programs in higher education at Banten Jaya University (UNBAJA). Thematic KKM activities, is one form of integrating education, research, and community service activities. The current KKM data processing system is that students come directly to the relevant work units to register and report, Field Supervisors are also parties associated with KKM participants when collecting KKM assessments and their journals must come directly to the relevant work units. The purpose of this research is to design a system for KKM data processing in order to facilitate students, Field Supervisors and other relevant parties. This research development method uses System Development Life Cycle (SDLC) with the Rapid Application Development (RAD) model. The proposed system is a KKM data processing system that is done computerized and online where students can register and report as well as Field Supervising Lecturers as well as easily collect assessments and journals provided by the system without coming directly to the relevant work units.